The effect of POFA as cement replacement material towards mechanical properties of aerated concrete - Siti Norbaya , Mustafa (2014)
Aerated concrete is homogenous compared with ordinary concrete because it does not contain coarse aggregate phase but showed wide variation in properties. The main advantage of aerated concrete is lighter than normal concrete. This lightweight concrete can make the construction work done more easily and quickly. In addition, the design of structures such as foundations, column and beams can be reduced. Malaysia is the major palm oil exporter and has been facing problem in disposing palm oil fuel ash since many years ago. The challenge to produce Palm Oil Fuel Ash (POFA) by a palm oil processing factory will take a very long time. In this study, POFA was used as a pozzolanic material in concrete. A portion of Ordinary Portland Cement (OPC) was replaced by POFA at 0 %, 10 %, 20 % and 30 % by weight to reduce the cement. Compressive strength, modulus of elasticity, drying shrinkage and degree of hydration of concretes containing ground POFA were tested. The rate of hydration of cement and POFA has been tested to know the reaction of concrete hydration. The results showed the compressive strength of concrete is influenced by POFA content and the curing period with a 20 % replacement of POFA as partial cement to produces the higher strength compared to other mixtures. In addition, there was also a strong correlation between the compressive strength and the drying shrinkage of the POFA concrete. As a conclusion, the overall result for all testing conducted showed that the concrete with 20 % replacement of POFA material give the best result compared to control, 10 % POFA and 30 % POFA.